2010
DOI: 10.5194/adgeo-27-1-2010
|View full text |Cite
|
Sign up to set email alerts
|

Application of WaSiM-ETH model to Northern German lowland catchments: model performance in relation to catchment characteristics and sensitivity to land use change

Abstract: Abstract. The hydrological catchment model WaSiM-ETH (Water Balance Simulation Model) is a spatially distributed, process- and grid-based hydrological catchment model which was primarily developed to simulate the water balance of mountainous catchments. In this study, the ability of WaSiM-ETH was tested to describe the hydrological processes of lowland catchments. In addition, the resulting model performance was related to subcatchment characteristics and the model's sensitivity to possible future land use cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…influence of surface water on groundwater) are not met. Examples of the resulting problems are presented by Bormann and Elfert (2010), who used WaSiM-ETH (Schulla and Jasper, 2007) and Koch et al (2013), who used SWAT, both in northeastern Germany. Fan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…influence of surface water on groundwater) are not met. Examples of the resulting problems are presented by Bormann and Elfert (2010), who used WaSiM-ETH (Schulla and Jasper, 2007) and Koch et al (2013), who used SWAT, both in northeastern Germany. Fan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Simple, lumped hydrological models with a more traditional structure (i.e. without coupling and feedbacks) often fail to reproduce discharge dynamics in lowland catchments (Bormann and Elfert, 2010;Koch et al, 2013). Thus, instead of coupling existing models, hydrological models for application in lowland areas should be derived from a conceptually sound and strong coupling between groundwater and the unsaturated zone as well as between groundwater and surface water.…”
Section: Introductionmentioning
confidence: 99%
“…Gurtz et al 2003, Verbunt et al 2003, Jasper et al 2004, Leemhuis 2005, Jung 2006, Wagner et al 2009, Rößler and Löffler 2010, Rößler 2011. Bormann and Elfert (2010) reported that the model is a suitable tool for the simulation of the hydrological behaviour of lowland catchments. Habte et al (2007) indicated that the model satisfactorily simulates the hydrological behaviour for all sub-basin catchments of the Blue Nile basin in Ethiopia.…”
Section: Wasim-eth Modelmentioning
confidence: 99%